Wealth effects in the euro area - Cinzia Guerrieri; Caterina Mendicino (European Central Bank (ECB), 2018)
How sizable is the wealth effect on consumption in euro area countries? To address this question, we use newly available harmonized euro area wealth data and the methodology in Carroll et al. (2011b). We find that the marginal propensity to consume out of total wealth averaged across the largest euro area economies is around 3 cents per euro, with a marginal propensity to consume out of financial wealth significantly larger than of housing wealth. Country-group estimates document no significant differences between the largest economies and the rest of the sample. In contrast, remarkable differences emerge between periphery and core countries.
Keywords: C22; E21; E32; E44; 330; households wealth; financial assets; consumption dynamics; wealth effects